An overview of rain attenuation research in Bangladesh - Md Abdus Samad; Md. Razu Ahmed; Syed Zahidur Rashid (Institute of Advanced Engineering and Science, 2021)
The demands of shifting to the operating frequency of wireless telecommunication systems at new higher frequency bands increase as day by day the necessity to transfer more data volume through wireless networks. Bangladesh has launched its first satel-lite, Bangabandhu-1, with 40 communication channels in the C and Ku frequency bands. Besides, a huge volume of terrestrial microwave backbone networks suffer from fading during rain across the country. Bangladesh experiences heavy rainfall in June-July-August. The rain has a remarkable impact on deteriorating the signal-to-noise ratio at the receiver end. To implement the 5G network, 2.6–60 GHz frequency bands are promising. However, the propagated waves in these bands are prone to fadedue to rain. Unfortunately, the rain attenuation model developed for other climatic conditions can not be used readily without customization. In this regard, to maintain quality telecommunication networks, proper rain attenuation model development is crucial. This work reviews rain attenuation research in Bangladesh, global research trends and the research scope to manage rain attenuation.